Can Fraud Hexagon Detect Financial Statement Fraud in Healthcare Sector Companies in Indonesia? - Azizah, Widyaningsih; Andamari, Basis Gumilarsih; Ilham, Havian Muhammad (SEAN Institute, 2024)
With increasing financial statement fraud cases, measures to detect and prevent fraud are needed. Vousinas developed the fraud hexagon theory to detect manipulation in financial reports[1]. This research aims to empirically test the six dimensions of the fraud hexagon, namely pressure, opportunity, rationalization, capability, arrogance, and collusion, which is proxied by personal financial need, ineffective monitoring, change in auditor, change of board of directors, frequent number of CEO's picture, and political connections which are hypothesized to influence the occurrence of financial statement fraud. F-Score is used to determine fraudulent financial statements. The research population is health sector manufacturing companies listed on the Indonesia Stock Exchange during 2019 - 2021. The research sample consisted of 15 companies using purposive sampling. Hypothesis testing uses logistic analysis with the eviews10 application software. This research shows that personal financial need, ineffective monitoring, change in auditor, change of board of directors, and frequent number of CEO's pictures do not significantly affect financial report fraud. In contrast, political connections have a significant effect on financial report fraud.